Journal of human rights and the environment - Edward Elgar Publishing (Cheltenham, U.K. : Elgar Journals, 2010)
The relationship between human rights and the environment is a fascinating, uneasy, and increasingly urgent one. This international journal provides a strategic academic forum in which an extended interdisciplinary and multilayered conversation can take place concerning the challenges located at the interface of these two centrally important fields.
Special issue given in June 2012.
Mode of access: World Wide Web.
Description based on: v. 1, no. 1 (2010); title from cover.
Latest issue consulted: v. 4, no. 2 (2013).
Keywords: Human rights -- Environmental aspects -- Periodicals; Environmental policy -- Periodicals; Environmental law -- Social aspects -- Periodicals